STANDAR PELAYANAN PUBLIK PADA KANTOR DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU - RUSTAM, SUCI CAHYANI; Larissa, Dea (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2025)
This research aims to determine the fulfillment of standard components of public services. The problem in this research is that several components of public service standards have not been met. The research method used is qualitative field research, by conducting observations and interviews. The results of this research show that the fulfillment of the standard components of public services at the investment office and one-stop integrated services has been fulfilled, but the facilities need to be equipped, such as breast milk rooms, public toilets, prayer rooms and information screens.